THE IMPORTANCE OF THE SPEECH OF EDUCATORS AND EDUCATORS IN THE EDUCATIONAL PROCESS - Rimbayeva Ozoda Bazarbayevna (Journal of Artificial Intelligence and Digital Economy, 2024)
The factor that has the greatest impact on education in the educational process is the educator. In addition, in preschool educational institutions, educators are engaged in the education of children. It is important for educators and educators how much they have mastered communication skills when working with children and how much speech indicators have developed in the delivery of their own opinion and information. This article will talk about how significant the speech of educators and educators is in the educational process